(untitled) (The Review of Diabetic Studies, 2025)
This study investigates the psychological, social, and ethical dimensions of the illegal use of emergency services. Through a mixed-method field study involving emergency service records, psychological evaluations, and interviews with paramedics and psychologists, the research examines how psychological manipulation, malingering, and fabricated emergencies exploit limited emergency resources. Findings reveal a complex interplay between genuine mental health crises and intentional exploitation behaviors driven by attention-seeking, secondary gain, or antisocial tendencies. The paper highlights the ethical challenges faced by paramedics in distinguishing between legitimate distress and deceit, emphasizing the need for psychological screening tools, legal accountability, and public education to protect emergency infrastructure. Recommendations include integrating psychological assessment protocols into pre-hospital triage systems and fostering collaboration between emergency medical services (EMS) and mental health professionals. This study contributes to both psychological and emergency management literature by bridging the gap between behavioral analysis and operational ethics in the misuse of emergency systems.